2015
DOI: 10.1038/srep11350
|View full text |Cite
|
Sign up to set email alerts
|

Association between Int7G24A rs334354 polymorphism and cancer risk: a meta-analysis of case-control studies

Abstract: Accumulating evidences have suggested the potential association between Int7G24A (rs334354) polymorphism and cancer risk. However, results from epidemiological studies are controversial. We thus conducted this meta-analysis to clarify the association. Relevant studies were identified on electronic databases according to the inclusion criteria. A total of 13 case-control studies containing 4092 cases and 5909 controls were included in our meta-analysis. Odds ratios (ORs) with 95% confidence intervals (CIs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…The same study also reported one somatic mutation, resulting in a change of serine to phenylalanine at codon 57 of TGFBR1 [141]. Interestingly, the Int7G24A SNP is also associated with increased risks of osteosarcoma [179], colorectal, and breast cancer [180,181], suggestive of its general involvement in cancer predisposition.…”
Section: Bladder Cancermentioning
confidence: 79%
“…The same study also reported one somatic mutation, resulting in a change of serine to phenylalanine at codon 57 of TGFBR1 [141]. Interestingly, the Int7G24A SNP is also associated with increased risks of osteosarcoma [179], colorectal, and breast cancer [180,181], suggestive of its general involvement in cancer predisposition.…”
Section: Bladder Cancermentioning
confidence: 79%
“…Nevertheless, previous studies showed that Int7G24A polymorphism of gene TGF-b1 was significantly associated with cancer development in Asians, not in Caucasians. 26 TGF-b1 T869C/T29C polymorphisms were markedly associated with postmenopausal osteoporosis risk in Asians, not in Caucasians. 27 CC genotype and T allele of TGF-b1 T869C polymorphism were distinctly associated with diabetic nephropathy risk in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…This scale allocated a total score of 9 points, considering the selection process, the comparability of included studies, the identification of exposure and the definition of outcomes. The estimated scores of the included studies would be used in a quality-effect model [ 27 , 28 ], a method of weighting studies with quality scores to reduce the biases resulting from low quality studies. The results from the quality-effect model were introduced to explore the sensitivity and stability of our conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…In order to choose the best-fitted effect model, heterogeneity was first evaluated in our meta-analysis. If heterogeneity was acceptable and negligible, a fixed-effect modeling method would be used in the analysis, otherwise a random-effect modeling method would be suggested [ 28 , 29 , 30 ]. I 2 statistic and Cochran Q test were applied to estimate the heterogeneity among the identified studies [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation